Secondary Full-thickness Macular Holes after Diabetic Vitrectomy: Clinical Manifestations and Rational Approaches to the Treatment - Yun Hsia; Chung-May Yang; Yi-Ting Hsieh; Lu-Chun Wang (Journal of Ophthalmology)
Purpose. The aim of the study is to present the clinical characteristics and surgical treatment of secondary full-thickness macular hole (MH) after diabetic vitrectomy (DV) in patients with proliferative diabetic retinopathy (PDR). Methods. In this retrospective, observational, and longitudinal study, we enrolled consecutive patients with PDR who developed MH after DV. The macular structure was evaluated using optical coherence tomography. The clinical characteristics, surgical techniques, and outcomes were also recorded. Results. Three patients developed MH within 6 weeks, which was associated with foveal thinning, residual fibrovascular proliferation, or anterior proliferative vitreoretinopathy. Six patients developed MH originating from the epiretinal membrane (ERM) with lamellar MH (LMH) after a median interval of 16.5 months. Three of them were complicated with retinal detachment (RD). Various surgical procedures were performed according to the clinical scenarios, including internal limiting membrane (ILM) peeling, inverted ILM flap insertion, temporal inverted ILM flap, lens posterior capsular flap insertion, and neurosensory retinal free flap insertion. All patients achieved MH closure after surgery, and 5 patients exhibited improved visual acuity. Conclusions. MH may develop after successful DV, with a high rate of associated RD. Rapid MH formation was attributed to unreleased tractional force and weakened foveal structure. The development of ERM and LMH also led to MH. Various surgical techniques could be used for MH closure.